MALEAKHI 3:6-12 DAN PRAKTIK PERSEPULUHAN DI GEREJA: SUATU KAJIAN TEOLOGIS - Robi Prianto; Oferlin Hia; Yohanes Hasiholan Tampubolon; Doni Hariadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
The tithe practices in Indonesian churches are comprised of at least two views, namely those that mandate and those that do not mandate the offering. Churches that mandate the tithe offering are often based on the text of Malachi 3. The same text can also be a means of threat to those who do not give tithes, because the text writes about the curse that occurs as a result of disobedience. At the same time, there are also many opinions that underlie the non-obligation of the practice. Through exegetical methods, the writer found that the tithe practice encounters many difficulties in being applied according to regulations that are in accordance with the Bible. However, the tithe practice is actually a faith practice based on the main law, which is loving God and one another. The offering is not to obey religious regulations but as evidence of obedience to God and love for others. At the same time, this evidence of love can be based on the reality of the deepening socio-economic gap in Indonesia. Tithing can be applied to try to bridge the existing gap.